2005
DOI: 10.1080/03014223.2005.9518406
|View full text |Cite
|
Sign up to set email alerts
|

The home range of ship rats (Rattus rattus) in beech forest in the Eglinton Valley, Fiordland, New Zealand: A pilot study

Abstract: Three male and two female ship rats (Rattus rattus) were radio-tagged and tracked in beech (Nothofagus) forest in the Eglinton Valley, Fiordland, New Zealand over two field periods in 1996 and 2000. The home range of each animal was calculated using the minimum convex polygon method. Ranges of three male rats were 7.5, 9.1, and 11.4 ha whereas those of the female rats were 0.89 and 0.27 ha. The home ranges recorded for male rats were considerably larger than those reported from other studies in non-beech fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Home ranges of R. rattus in two montane mesic forests on O'ahu (1.5 -9.1 ha [Shiels 2010]) were nearly as variable as those in a South Island, New Zealand, beech forest (0.3 -11.4 ha [Pryde et al 2005]). Other New Zealand studies in North Island forests found that R. rattus home ranges were much smaller (e.g., 0.3 -1.8 ha in a study by Dowding and Murphy [1994], and 0.3 -2.2 ha in Hooker and Innes [1995]).…”
Section: Physiology and Behaviormentioning
confidence: 90%
“…Home ranges of R. rattus in two montane mesic forests on O'ahu (1.5 -9.1 ha [Shiels 2010]) were nearly as variable as those in a South Island, New Zealand, beech forest (0.3 -11.4 ha [Pryde et al 2005]). Other New Zealand studies in North Island forests found that R. rattus home ranges were much smaller (e.g., 0.3 -1.8 ha in a study by Dowding and Murphy [1994], and 0.3 -2.2 ha in Hooker and Innes [1995]).…”
Section: Physiology and Behaviormentioning
confidence: 90%
“…Ship rats live entirely in silver tussock grassland on the sub-antarctic Macquarie Island (Pye et al 1999) and recent anecdotal evidence from trapping operations suggests they are present in the New Zealand alpine zone at certain sites (O'Donnell et al 2017) which would be comparable ecologically with Mt Misery. Furthermore, male ship rats have been recorded moving distances of up to 790 m in a night in beech forest (Pryde et al 2005), so should be capable of living in the forest and commuting into the alpine zone. Overseas, while ship rats tend to be more abundant in temperate locations (Horskins et al 1998;Lindsey et al 1999;Wegmann et al 2008), they are also present in cold climatic zones like Macquarie Island where mean annual temperature is 4.9°C (Australian Government Bureau of Meteorology, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…New Zealand studies have been in forest habitats more complex than Taukihepa, where there is an almost monospecific canopy of tūpare over sparse ground cover. Tūpare trees lack cavities and epiphytes that usually provide forest-dwelling rats with potential den sites on the mainland (Best 1968;hooker & innes 1995;Pryde et al 2005). in contrast, there were a large number of possible den sites on the ground within burrows, logs, woodpiles, and ferns.…”
Section: Den Site Locationsmentioning
confidence: 99%
“…Rats have also been observed in den sites in flax bushes (Phormium spp.) and in pre-existing cavities at ground level (Best 1968;Pryde et al 2005). in hawaii ship rats dig burrow systems underground (flannelly et al 1986) or nest in porous lava (Tobin et al 1996) or up trees.…”
Section: Den Site Locationsmentioning
confidence: 99%
See 1 more Smart Citation